Super-infection by multiple microorganisms in COVID-19 patients - Gomez, Andrea C.; Ortiz, Tamin; Valenzuela, Angélica; Egoávil-Espejo, Rocío; Huerto-Huanuco, Rosario; Pinto, Joseph A.; Lagos, Jose; Ruiz, Joaquim (Frontiers in Molecular Biosciences, 2023)
Introduction: This study aimed to describe the clinical characteristics of patients with COVID-19 co-infected with multiple multidrug-resistant bacteria. Methods: Patients hospitalized in the AUNA network between January and May 2021, diagnosed with COVID-19 and at least two other infecting microorganisms, were retrospectively included in the analysis. Clinical and epidemiological data were extracted from clinical records. The susceptibility levels of the microorganisms were determined using automated methods. Antibiotic resistance was established among infecting bacteria accounting for ≥5 isolates. Results: A total of 27 patients (21 male and 6 female patients) met the inclusion criteria, with a maximum of eight co-infecting bacteria or fungi during admission time. Seven patients (25.9%) died, with a higher but not significant lethality among women (50% vs. 19.0%). A total of 15 patients presented at least one established comorbidity, with hypertension being the most frequent. The time elapsed between COVID-19 diagnosis and hospital attendance was 7.0 days, with that of patients with a fatal outcome being longer than that of living patients (10.6 vs. 5.4). Up to 20 different microorganisms were isolated, with Pseudomonas aeruginosa being the most common (34 isolates). In general, antibiotic resistance levels were high, especially in Acinetobacter baumannii isolates, with resistance levels of 88.9% to all antimicrobial agents tested, except colistin (0%). Conclusion: In conclusion, the present results show the presence of multiple microorganisms that co-infect COVID-19 patients. When fatal outcome rates are in the range of other reports, the presence of a series of multidrug-resistant microorganisms is of concern, showing the need to reinforce control measures to limit the expansion of almost untreatable microorganisms.